THE EFFECT OF LEADERSHIP STYLE, JOB SATISFACTION, AND ORGANIZATIONAL COMMITMENT TOWARD TURNOVER INTENTION ON BALAI PENDIDIKAN DAN PELATIHAN ILMU PELAYARAN (BP2IP) HUMAN RESOURCES EMPLOYEES DIVISION - Hidayat, Benny; Zusi, Hasmand; G, Andreas Wahyu (Jurnal Maritim Malahayati, 2021)
The background of this research was examined the relationship among leadership style, job satisfaction, organizational commitment, and turnover intention of employees. A model of job satisfaction, organizational commitment, and turnover intention is developed and tested in one field study. The objectives of this research was analyzed the effect of negatively leadership style on turnover intention, the effect of negatively job satisfaction on turnover intention, the effect of organizational commitment on turnover intention, the effect of negatively leadership style and organizational commitment on turnover intention. A sampling with purposive sampling techniques of eighty four employees of human resource division for distributing the questionnaire in company. This research uses a multiple regression analyses with SPSS ver. 17 to test four hypotheses. The result of this research concludes that is the effect of negatively leadership style, job satisfaction, organizational commitment, and turnover intention of employees.